STUDIES ON ANTIMICROBIAL ACTIVITY, PHYTOCHEMICAL SCREENING TESTS, BIOCHEMICAL EVALUATION OF CLITOREA TERNATEA LINN. PLANT EXTRACTS - Chakraborty, Sriyeta; Sahoo, Souvagyalaxmi; Bhagat, Anjana; Dixit, Sangita (International Journal of Research -GRANTHAALAYAH, 2017)
The Clitoriaternatea medicinal plant deserves multipotent bioactive secondary metabolites potentials in a great deal. The aim of this study is to analyze the phytochemical, biochemical and antimicrobial activities of the different plant extracts. Extracts from the leaves and seed of Clitoriaternatea were extracted with water and methanol. Phytochemical analysis observed the presence of flavonoids, Carbohydrates, phenols, saponins, tannins, quinines, terpenoids and oxalate components in leaves and seed extract of methanol. In seeds aqueous and methanol extracts, alkaloids, carbohydrates, glycosides, flavonoids, tannins, saponins, amino acids, proteins, terpenoids were present. Quantitatively, seed and leaves methanol extract have good quantity of phenol, carbohydrates, tannin, flavonoid and terpenoid. Two bacterial and fungal strains were taken for antimicrobial analysis. The antibacterial study against E.coli and B.subtlis, result in the zone of inhibition which was more in case of methanol extracts. In antifungal analysis, the extracts were showed equally effective against A.niger whereas the seeds methanol extracts were little more effective against in case of P.chrysogenum. Hence, C. ternatea can be used to discover bioactive natural products that may serve as a base in the development of new natural plant-based medicine.